Pelaksanaan Pembelajaran Sastra di Era Kurikulum Merdeka dalam Perspektif Strenght, Weakness, Opportunities, Threath (SWOT) - Pratiwi, Putri Endah; Hartono, Hartono; Efendi, Anwar (STKIP Singkawang, 2025)
The learning of literary is very important because with literary, students can develop thinking abilities, skills, and increase sensitivity through character. However, literary learning is often only a supporting material for Bahasa Indonesia which tend to be ignored. This research aims to reveal the strengths, weaknesses, opportunities, and threats of literary learning in the Kurikulum Merdeka. This research is a descriptive qualitative research with primary data sources being information obtained from teachers and students of five high schools in East Belitung Regency through observation, questionnaires, and interviews. Meanwhile, secondary data sources are obtained through analysis of documents accompanying learning, such as modules and evaluation result data. The data were then analysed using the Miles, Huberman and Saldana model. The results of the analysis show that literary learning in the Kurikulum Merdeka has strengths, namely being bound by the curriculum, innovative learning strategies, and technological support. The weaknesses of literary learning lie in the small portion of material, shallow learning, and technology without restrictions. The opportunities for literary learning lie in teacher flexibility and school support. The threats to literary learning that pose a challenge are suboptimal literary learning outcomes, low teacher competence, motivation, and inappropriate learning objectives.